ISPC Assessment of Flagship 2: Trees for Smallholder Livelihoods - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
Assessment of Flagship 2 (Trees for smallholder livelihoods) of the CGIAR Research Program on Forests, Trees, and Agroforestry (2017-2022). Flagship 2 (trees for smallholder livelihoods) of the Forests, Trees and Agroforestry CRP aims to offer options for improved food security and livelihood outcomes through improvements in the management of: natural resources; timber and non-timber forest product production; tree-crop systems; pastures; and through the diversification of production systems.